2017
DOI: 10.18869/nrip.irj.15.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Work-related Musculoskeletal Disorders and Injuries in Occupational and Physical Therapists and Its Comparison

Abstract: Objectives: Musculoskeletal disorders (MSD) are the most prevalent occupational diseases that are serious, fundamental and costly in nature.Methods: This analytical descriptive study included 45 individuals of occupational and physiotherapy community in Hamedan, Nahavand and Malayer cities of Iran.The standardized Nordic questionnaire was used to collect data. Data analysis was done by SPSS software, chi-square test, T-test and Kay Score tests. Results:Study results revealed the prevalence of MSD accounting fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
2
3
0
Order By: Relevance
“…In our study, a significant statistical relationship was found between WRMDs in the wrist area and performing a manual massage, myofascial release, mobilization, muscle energy technique, and taping. This finding agrees with other studies that have linked the use of manual therapy techniques such as massage to wrists and hands symptoms [20,25,30]. Alrowayeh et al [31], however, found no significant association between job factors and increased workrelated musculoskeletal injuries.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In our study, a significant statistical relationship was found between WRMDs in the wrist area and performing a manual massage, myofascial release, mobilization, muscle energy technique, and taping. This finding agrees with other studies that have linked the use of manual therapy techniques such as massage to wrists and hands symptoms [20,25,30]. Alrowayeh et al [31], however, found no significant association between job factors and increased workrelated musculoskeletal injuries.…”
Section: Discussionsupporting
confidence: 88%
“…There was a significant relationship between gender and incidence of WRMDs, which is consistent with the study of Adegoke et al They identified female gender as a factor in the development of musculoskeletal disorders [17]. However, it was against the results of Salik and Özcan, Sharhaninezhad et al, and Nazari et al [16,19,20]. Adegoke et al and Glover et al reported that in the first 5 years of employment, musculoskeletal injuries are more common [14,17].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…MSDs often engage multi-risk factors. The most important risk factors include vibration [7], poor posture, repetitive and excessive force, lifting and carrying [8][9][10][11]. The awkward posture is most important among various risk factors [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Those jobs with manual handling tasks are at risk of ergonomics problems [7,8]. WRMSDs are involved with various organs of the body like neck, shoulder, arms, and the back [9,10].…”
Section: Introductionmentioning
confidence: 99%